The Influence of Field Work Practices, Motivation, and Self-Efficacy on Work Readiness - Haq, Daffak Amirul; Adiwati, Mei Retno (International Journal of Economics (IJEC), 2024)
Job readiness is the ability of a human being to do things related to work activities. Job readiness is a trait and behavior that will be needed by students, especially final year students. To build job readiness, it is also necessary to practice field work, motivation and self-efficacy of students. This research is a type of quantitative research. This study made a sample of final year Management students Faculty of Economics and Business, UPNV East Java The sample technique used was Simple Random Sampling with a total of 94 students and data analysis techniques using the PLS (Partial Least Square) method, using validity tests, reliability tests, and hypothesis tests. The results of previous research on research related to the variables of this study show that there is a positive and significant influence on the influence of field work practices, motivation, and self-efficacy on work readiness.